Ecclesial Politology: in Search of an Adequate Perspective of Viewing the Church in Political Studies - Tadeusz SDS Jarosz (Chrześcijaństwo-Świat-Polityka)
Transformations in the theoretical and methodological inventory of political science define the framework of reflections on the present state of studies on the institutionality of the Church. Analyses revealing the insufficiency of approaches proposed so far confirm the need for a more adequate perspective of research into its individual aspects. This perspective is created by the normative theological and philosophical content which defines the extent component of the concept of Church. Empirically derived descriptions of the individual elements making up this concept, on the other hand, performed within the domain of social sciences, add precision to its definition content-wise. A skillful combination of the two aspects of the concept of Church offers a more in-depth insight into the functioning of ecclesial institutions by emphasizing the supernatural element as a component of the social and political process.